Effect of Intensive and Standard Clinic‐Based Hypertension Management on the Concordance Between Clinic and Ambulatory Blood Pressure and Blood Pressure Variability in SPRINT. Issue 14 (16th July 2019) - Ghazi, Lama; Pajewski, Nicholas M.; Rifkin, Dena E.; Bates, Jeffrey T.; Chang, Tara I.; Cushman, William C.; Glasser, Stephen P.; Haley, William E.; Johnson, Karen C.; Kostis, William J.; Papademetriou, Vasilios; Rahman, Mahboob; et al.
Abstract : Background: Blood pressure (BP) varies over time within individual patients and across different BP measurement techniques. The effect of different BP targets on concordance between BP measurements is unknown. The goals of this analysis are to evaluate concordance between (1) clinic and ambulatory BP, (2) clinic visit‐to‐visit variability and ambulatory BP variability, and (3) first and second ambulatory BP and to evaluate whether different clinic targets affect these relationships. Methods and Results: The SPRINT (Systolic Blood Pressure Intervention Trial) ambulatory BP monitoring ancillary study obtained ambulatory BP readings in 897 participants at the 27‐month follow‐up visit and obtained a second reading in 203 participants 293±84 days afterward. There was considerable lack of agreement between clinic and daytime ambulatory systolic BP with wide limits of agreement in Bland‐Altman plots of −21 to 34 mm Hg in the intensive‐treatment group and −26 to 32 mm Hg in the standard‐treatment group. Overall, there was poor agreement between clinic visit‐to‐visit variability and ambulatory BP variability with correlation coefficients for systolic and diastolic BP all <0.16. We observed a high correlation between first and second ambulatory BP; however, the limits of agreement were wide in both the intensive group (−27 to 21 mm Hg) and the standard group (−23 to 20 mm Hg). Conclusions: We found low concordance in BP and BP variability between clinic and ambulatory BP and second ambulatory BP. Results did not differ by treatment arm. These results reinforce the need for multiple BP measurements before clinical decision making.